School psychology and inclusive education: from graduation to psychologists school pratices from Mato Grosso do Sul - Altrão, Suéllen Soares (2019)
This article results from a study that aimed to knowing conceptions and practices of school psychologists related to Inclusive Education.  Thefore, it evidences the training and work of professionals institutionally linked to municipal education networks of municipalities in southern Mato Grosso do Sul: Ivinhema, Batayporã and Glória de Dourados.  By means of qualitative research in the case study modality, we tried to understand the influences to choosing onto School and Educational Psychology, professional qualification processes for acting in this field, as well as the challenges faced in their paths for the promotion of inclusion school systems they work with.  The results suggest an inexpressive presence of school psychologists working in the region. Besides that, professionals acting in this area have been facing difficulties into planning and implementing inclusives educational practices construction, despite their knowledge about inclusion.